Charge Sheet Super Junction in 4H-Silicon Carbide: Practicability, Modeling and Design - K. Akshay; Shreepad Karmalkar (IEEE Journal of the Electron Devices Society)
We discuss details of the Charge Sheet SuperJunction (CSSJ) in 4H-Silicon Carbide (SiC). This device was earlier proposed in Si material. A CSSJ is obtained by replacing the p-pillar of a SJ by a bilayer insulator, e.g., Al2O3/SiO2; the inter-layer interface of this insulator has a negative charge-sheet, whose magnitude is easily controlled via the insulator deposition temperature. This charge-sheet depletes the n-pillar. Two potential advantages of this structural modification are brought out. First, it can avoid the problems related to SiC SJ’s p-pillar fabrication. Second, it can lower the specific-on resistance, $R_{ONSP}$ , below that of SJ by 5–45 %, since SiC technology allows the insulator to be thinner than the p-pillar. The critical field, $E_{C}$ , in SiC is > 10 times higher than that in Si. We give an analytical breakdown voltage, $V_{BR}$ , model, which shows that the $V_{BR}$ sensitivity to charge imbalance due to inevitable process variations is inversely proportional to $E_{C}$ ; hence, this sensitivity of CSSJ in SiC is > 10 times lower than that in Si. On the other hand, we give numerical simulations to establish that, in spite of $E_{C}$ differences, the SiC CSSJ inherits the advantage of upto 15% higher $V_{BR}$ compared to SiC SJ, from its Si counterparts. We show how our prior analytical procedure of designing a SJ can be adapted to design a CSSJ having a lower $R_{ONSP}$ than the SJ, at a specified $V_{BR}$ in 1–10 kV range and charge imbalance ≤ 20 %. Our work should strengthen the motivation for fabricating the CSSJ in SiC.